Especies del Orden Clypeasteroida (Echinodermata: Echinoidea) de las costas de Venezuela - Francisco, V. (2008)
Species of the Order Clypeasteroida (Echinodermata: Echinoidea) from the Venezuela coasts. In Venezuela, taxonomic studies of echinoids are scarce, and most of the information is scattered in bibliographic sources or in collections from scientific expeditions deposited in foreign museums. With the aim to compile information about the species diversity of the Order Clypeasteroida (Class Echinoidea), which occur along the Venezuelan coast, we conducted a bibliographic revision, that was complemented with data from echinoderm collections from the Museo de Biología of the Universidad Central de Venezuela, and data bases from the Museo Oceanológico “Benigno Román” (Fundación La Salle de Ciencias Naturales, Venezuela), the Smithsonian National Museum of Natural History (Washington D.C.) and the California Academy of Sciences. At present, there are ten species belonging to the Order Clypeasteroida in Venezuela. Six of them belong to the Family Clypeasteridae: Clypeaster cyclopilus, C. euclastus, C. lamprus, C. prostratus, C. rosaceus and C. subdepressus, and four species belong to the Family Mellitidae: Encope emarginata, E. michelini, Leodia sexiesperforata and Mellita quinquiesperforata. We present a diagnosis for each of the ten species based on morphological characteristics with illustrations of the most common species. Rev. Biol. Trop. 56 (Suppl. 3): 215-228. Epub 2009 January 05.